2020
DOI: 10.1002/pro.3914
|View full text |Cite
|
Sign up to set email alerts
|

Using physical features of protein core packing to distinguish real proteins from decoys

Abstract: The ability to consistently distinguish real protein structures from computationally generated model decoys is not yet a solved problem. One route to distinguish real protein structures from decoys is to delineate the important physical features that specify a real protein. For example, it has long been appreciated that the hydrophobic cores of proteins contribute significantly to their stability. We used two sources to obtain datasets of decoys to compare with real protein structures: submissions to the bienn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 77 publications
0
8
0
Order By: Relevance
“…In summary, when we analyze all structures in the PDB determined by NMR, for which restraint data is available, they on average possess smaller, more densely packed cores compared to high-resolution x-ray crystal structures. Interestingly, smaller, but more densely packed cores have also been found in many computationally generated low-scoring structures with incorrect backbone placement submitted to the Critical Assessment of protein Structure Prediction (CASP) competitions 14 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, when we analyze all structures in the PDB determined by NMR, for which restraint data is available, they on average possess smaller, more densely packed cores compared to high-resolution x-ray crystal structures. Interestingly, smaller, but more densely packed cores have also been found in many computationally generated low-scoring structures with incorrect backbone placement submitted to the Critical Assessment of protein Structure Prediction (CASP) competitions 14 .…”
Section: Resultsmentioning
confidence: 99%
“…In previous work, we analyzed a non-redundant set of high-resolution x-ray crystal structures (with resolution < 1.8 Å) and found that the cores (residues with zero solvent accessible surface area) of these proteins represent about 8% of the total number of residues in the protein. In addition, the packing fraction, φ, in protein cores is ∼ 0.55 ± 0.01 13,14 . In earlier work, using a subset of NMR structures with a large number of distance restraints per residue, we concluded that the cores of NMR-determined protein structures had a higher packing fraction than those of high-resolution protein structures determined by x-ray crystallography 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, smaller, but more densely packed cores have also been found in many computationally generated lowscoring structures with incorrect backbone placement submitted to the Critical Assessment of protein Structure Prediction (CASP) competitions. 26 To investigate the discrepancies in the core packing properties in greater detail, we compared protein structures that had been determined by both X-ray crystallography and NMR. We assembled a data set of 702 pairs with both a high-resolution X-ray crystal structure (<2.0 Å) and an NMR structure with available restraints, where the pairs have >90% sequence similarity.…”
Section: Resultsmentioning
confidence: 99%
“…However, one must be able to identify when the REMD simulation is close to the experimental structure, without knowing the experimental structure beforehand. The distance to the x-ray crystal structure can be estimated using protein decoy detection methods [14,[21][22][23], which have their own limitations, and would limit the ability of REMD to identify experimental conformations. It is likely that the CHARMM36m forcefield possesses low-lying energy minima that are distinct from those sampled by x-ray crystal structures.…”
Section: (G)-(i)mentioning
confidence: 99%
“…The algorithm takes z-slices of the protein, determines the solvent accessibility of the sets of contours using a probe molecule of a given radius, and integrates the SASA over the slices. We use a water-molecule-sized probe with radius 1.4 Å and z-slices with thickness ∆z = 10 −3 Å, which were used in previous work [11,14,34,48,49]. To normalize the SASA, we take the ratio of the SASA within the context of the protein (SASA context ) and the SASA of the same residue X extracted from the protein structure as a dipeptide (Gly-X-Gly) with the same backbone and side-chain dihedral angles:…”
Section: Relative Solvent Accessible Surface Areamentioning
confidence: 99%